Perbandingan antara Hukum Zakat dan Wakaf dalam Perspektif Fikih Kontemporer - Khusnul Khatimah; Muhammad Sahdan Siregar; Yuliana Fatmawati; Desty Novita Sari; Ali Murtadho Emzaed (Hidayah : Cendekia Pendidikan Islam dan Hukum Syariah, 2025)
This research aims to deeply understand the legal differences between zakat and waqf from the perspective of contemporary fiqh, as well as to analyze their relevance and application in the context of modern social, economic, and technological settings. This research uses a comparative analysis method with a descriptive qualitative approach based on literature study. The sources examined include classical fiqh literature from the four schools of thought, contemporary scholars' views, as well as modern regulations and fatwas related to zakat and waqf in Indonesia. The research findings indicate that although zakat and waqf have fundamental differences in legal status, form, and purpose of utilization, both share a common spirit of wealth distribution and community empowerment. Moreover, contemporary issues such as professional zakat, corporate zakat, stock zakat, cash waqf, productive waqf, and digitalization highlight the need for institutional renewal and strengthening to ensure that the laws of zakat and waqf remain relevant and effective in the modern era. This research concludes that understanding and managing zakat and waqf in an adaptive manner to the times is very important in realizing sustainable community welfare.